The role and impact of CCTV operators in contributing to efficient crime prevention: a case study of surveillance operators within the City of Cape Town - Papale, Phelimon (Department of Public Law, 2024)
It is widely recognised that technology has become a critical tool in the business of crime control and prevention. The main purposes of closed-circuit television (CCTV are the detection and deterrence of crime in pursuit of public safety and security. Highways, shopping centres, workplaces, and public transportation systems are all frequent sites for CCTV surveillance. However, studies have consistently fallen short in examining the role and responsibilities of CCTV operators in attempts to detect and deter crime via surveillance systems. Any assertions concerning the overall effectiveness of CCTV cameras, especially when doing proactive real time monitoring, depend on how the cameras are operated, controlled, and monitored by human agents. This minor dissertation explores the views and experiences of CCTV operators regarding their role and functions in contributing to crime detection and prevention. The research explored the routine responsibilities of operators, how they perceive their role in the quest for community safety and the challenges related to their work environment. Utilising a qualitative research approach, face-to-face interviews were held with a sample of 15 CCTV operators from the City of Cape Town CCTV Control Centres. Thematic analysis guided data analysis. The findings revealed that most CCVT operators understood their role as monitoring and detecting unlawful actions and, in doing so, enhancing community safety. Such actions are performed through live recordings, proactive monitoring, and reacting to identified safety threats. Several occupational challenges impacting their everyday work were identified. These included technical and social challenges related to the work of CCTV operators, as well as poor relations with the South African Police Service. By way of conclusion, some recommendations are offered to improve the working environment of CCTV operators and address cognitive challenges.